Is offshoring linked to offshoring potentials? Evidence from German linked-employer-employee data - Tobias Brändle (Institut für Angewandte Wirtschaftsforschung (IAW), 2014)
This paper analyses the link between offshoring in German plants and the offshoring potential of their employees. We use information on the offshoring potential of jobs from representative task data and merge it with linked employer-employee data, for which information on different modes of offshoring behaviour is available. We empirically identify individual and plant-level determinants of offshoring activity and additionally analyse how offshoring potential influences the realisation of offshoring by German plants. Depending on the measure for actual offshoring, we mostly find a negative link: firms are less likely to outsource or offshore parts of their production processes if their outsourcing and offshoring potential is high. This indicates that existing measures of offshoring potential can indeed be interpreted as not-yet realised offshoring, or offshoring that cannot be realised, e.g. due to trade barriers.
Keywords: F14; F16; 330; Outsourcing; Offshoring; Trade in Tasks